2022
DOI: 10.3389/fpls.2022.1008624
|View full text |Cite
|
Sign up to set email alerts
|

Different adaptive patterns of wheat with different drought tolerance under drought stresses and rehydration revealed by integrated metabolomic and transcriptomic analysis

Abstract: Wheat as a staple food crop is enduring ever-frequent intermittent and changing drought with the climate change. It is of great significance to highlight the adaptive approaches under such variable conditions at multiple levels to provide a comprehensive understanding of drought tolerance and facilitate the genetic breeding of wheat. Therefore, three wheat lines with different drought tolerance (drought-tolerant mutant Mu > common wheat CK > drought susceptible mutant mu) were analyzed under mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…This further supports the idea that I. difengpi , experiencing drought stress, induces stomatal closure to reduce transpiration and consequently decreases photosynthetic capacity. Similar findings have been reported in wheat ( Lv et al., 2022 ). When I. difengpi plants were watered again, a majority fraction of photosynthesis-related genes were upregulated, indicating gradual recovery of photosynthesis-related processes from drought stress after rehydration.…”
Section: Discussionsupporting
confidence: 91%
“…This further supports the idea that I. difengpi , experiencing drought stress, induces stomatal closure to reduce transpiration and consequently decreases photosynthetic capacity. Similar findings have been reported in wheat ( Lv et al., 2022 ). When I. difengpi plants were watered again, a majority fraction of photosynthesis-related genes were upregulated, indicating gradual recovery of photosynthesis-related processes from drought stress after rehydration.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we selected a wheat variety Jimai 418, known for its drought characteristics and yield stability [47]. Field pot experiments were conducted at the experimental station of Hebei Agricultural University (Gaocheng County, Shijiazhuang, China), which is a major wheat-producing area in the Huang-Huai-Hai Plain (38.03 • N, 114.84 • E, 56 m above sea level).…”
Section: Plants and Experimental Sitementioning
confidence: 99%
“…In recent years, several studies have combined metabolomics and transcriptomics analyses to clarify the mechanisms underlying metabolite biosynthesis in plants [41][42][43][44][45][46]. One study analyzed three wheat lines with varying drought tolerance using transcriptomic and metabolomic approaches under moderate and severe drought conditions and revealed that increased antioxidant activity and flavonoid content led to enhanced amino acid biosynthesis and ROS scavenging under drought stress [47].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolome is a bridge connecting the changes between plant transcriptomes and phenotypes. Integrated analyses of transcriptomes and metabolomes are now widely used to identify key differences in regulatory mechanisms between stress-tolerant and -sensitive genotypes displaying differential phenotypes, and relevant studies have shown that plants respond to drought stress mainly by regulating oxidative balance, signal transduction, plant hormones and energy metabolism [24][25][26][27][28]. In sweet potato, transcriptomics has become a powerful tool for examining various mechanisms, such as potassium-deficiency tolerance [29], skin color [30], and stem nematode resistance [31].…”
Section: Introductionmentioning
confidence: 99%